Sosialisasi Desain Infiltration Trench Sebagai Upaya Pengendalian Banjir Di Hatyai, Songkhla - Yulia; Manovri Yeni; Effendi Nurzal; Ira Dama Yanti (Bansigom Na Publisher, 2024)
Frequent flooding in Hatyai, Songkhla, Thailand, has become a serious threat to local communities. Although various flood control efforts have been carried out through infrastructure, they have not been able to completely solve the existing problems. Therefore, the active involvement of the community is very important in reducing the risk of flooding. The purpose of this article is to explain the process of disseminating the infiltratetrench system design to the community in Hatyai, Songkhla as part of the Flood Risk Reduction Strategy. This socialization process involves preparation, preparation of materials, implementation, and evaluation. By involving the community directly in the understanding and application of the infiltratetrench system, it is expected to reduce the risk of flooding and increase community resilience to such disasters.